The “Drop of Honey Effect” metaphor in Chaos Theory - Ferreira, M. A. M.; Filipe, J. A. (Acta Scientiae et Intellectus, 2017)
Chaos theory resulted in great part from natural scientists’ outcomes in non-linear dynamics area. The prominence of associated models has increased in the last decades, due the non-linear systems temporal evolution study. Consequently, chaos is one of the concepts that most quickly have been expanded in what research topics concerns. In case of unstable relationships in non-linear systems, chaos theory aims to understand and explain this kind of unpredictable aspects of nature, social life, the uncertainties, the nonlinearities, the disorders and confusions. Scientifically it represents a disarray connection, but basically it involves much more. The close association between change and time seems essential to understand what happens in the fundamentals of chaos theory. This theory got a central role in the explanation of a lot of phenomena. The relevance of these theories has been well recognized in the clarification of social phenomena and has permitted new advances in the study of social systems. Chaos theory has also been applied, particularly in the context of politics, in this area. This work goal is to make a reflection on chaos theory – and also on dynamical systems and theory of complexity – in terms of the understanding of political issues, considering some events in the political context and also considering the macro-strategic ideas of states positioning in the international stage. In this line of reasoning the "Drop of Honey Effect" metaphor is presented, somewhat analogous to that of "Butterfly Effect", and the idea that it is better suited to portray social phenomena, in particular political phenomena, is defended.